2021
DOI: 10.1071/mf20381
|View full text |Cite
|
Sign up to set email alerts
|

Salvaging and replanting 300 mangrove trees and saplings in the arid Arabian Gulf

Abstract: Construction works along a causeway at Mubarraz Island near Abu Dhabi, United Arab Emirates, in the Arabian Gulf necessitated the salvaging and replanting of 300 mangroves (Avicennia marina). Mangroves were excavated manually by shovel (smaller trees and saplings) or mechanically using a backhoe excavator (larger trees), transported with the root ball wrapped in burlap and replanted in a newly created tidal channel. Relocated mangroves were exposed to two different watering regimes and two tidal inundation lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Indeed, previous studies involving Avicennia marina have shown that larger transplanted seedlings survive better than or equal to medium-sized individuals and exhibit greater increases in plant height and leaf production than small individuals [45]. Saplings, being the largest life stage typically used in mangrove restoration projects (except for the few studies that have employed adult trees [31]), appear more able to withstand higher exposure to waves and wind that often characterize fringing habitats [23]. It is interesting to note that there were no reported studies using the less-developed propagules of pencil-rooted mangroves (i.e., seed capsules or fruits), although it remains unclear as to whether this is due to recording bias or whether this is due to experience learned by practitioners.…”
Section: Methodological Considerations To Plantingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous studies involving Avicennia marina have shown that larger transplanted seedlings survive better than or equal to medium-sized individuals and exhibit greater increases in plant height and leaf production than small individuals [45]. Saplings, being the largest life stage typically used in mangrove restoration projects (except for the few studies that have employed adult trees [31]), appear more able to withstand higher exposure to waves and wind that often characterize fringing habitats [23]. It is interesting to note that there were no reported studies using the less-developed propagules of pencil-rooted mangroves (i.e., seed capsules or fruits), although it remains unclear as to whether this is due to recording bias or whether this is due to experience learned by practitioners.…”
Section: Methodological Considerations To Plantingmentioning
confidence: 99%
“…For each study, information was extracted in relation to the length of time plants were maintained in a nursery prior to planting, any reports of after-care, such as supplementary watering or the removal of debris, and the main reason for mortality, if available. After-care was defined as ongoing actions, such as monitoring, guarding the plantation to avoid improper use, removing plastic debris, restricting trampling and watering, all of which have been shown to enhance survival rates [30,31]. The reasons for mortality were grouped into five categories, described as: 'abiotic' (e.g., salinity, wave energy, light exposure), 'site suitability' (e.g., high or low inundation, planting area), 'competition' (e.g., nutrient limitation), 'predators' (e.g., monkeys, crabs, goats) and 'methodology' (e.g., use of artificial structures, plantation density), and the prevalence of these factors was calculated from all reported studies.…”
Section: Data Collection and Standardizationmentioning
confidence: 99%